Dentin Morphology of Root Canal Surface: A Quantitative Evaluation Based on a Scanning Electronic Microscopy Study. (27th August 2015) - Lo Giudice, Giuseppe; Cutroneo, Giuseppina; Centofanti, Antonio; Artemisia, Alessandro; Bramanti, Ennio; Militi, Angela; Rizzo, Giuseppina; Favaloro, Angelo; Irrera, Alessia; Lo Giudice, Roberto; Cicciù, Marco
Abstract : Dentin is a vital, hydrated composite tissue with structural components and properties that vary in the different topographic portions of the teeth. These variations have a significant implication for biomechanical teeth properties and for the adhesive systems utilized in conservative dentistry. The aim of this study is to analyse the root canal dentin going from coronal to apical zone to find the ratio between the intertubular dentin area and the surface occupied by dentin tubules varies. Observations were conducted on 30 healthy premolar teeth extracted for orthodontic reasons in patients aged between 10 and 14. A SEM analysis of the data obtained in different canal portions showed that, in the coronal zone, dentinal tubules had a greater diameter (4.32  μ m) than the middle zone (3.74  μ m) and the apical zone (1.73  μ m). The average number of dentinal tubules (in an area of 1 mm 2 ) was similar in coronal zone (46, 798 ± 10, 644 ) and apical zone (45, 192 ± 10, 888 ), while in the middle zone they were lower in number (30, 940 ± 7, 651 ). However, intertubular dentin area was bigger going from apical to coronal portion. The differences between the analysed areas must be considered for the choice of the adhesive system.